Factors influencing the use of shared e-scooters in Lille, France - Melendez Arrospide, Alvaro Martin (2025)
This thesis explores the factors influencing the use of shared e-scooters in Lille, France. Its main objective is to understand the key motivations, barriers, behavioral impacts, and necessary improvements for integrating shared e-scooter services. A qualitative methodology was applied, including interviews with users and experts, as well as focus group discussions with non-users. Findings show that convenience, speed, and environmental benefits are the primary drivers of e-scooter use. However, safety concerns, high costs for frequent use, and limited infrastructure remain major obstacles. Shared e-scooters have reduced reliance on cars, taxis, and buses for short trips, encouraging more efficient travel behavior. To support sustainable integration, the study recommends policy and infrastructure changes such as expanding dedicated lanes, increasing charging stations, implementing clear safety regulations, and offering more affordable pricing models. Integration with public transportation systems is also encouraged. The results offer valuable insights for policymakers and urban planners aiming to promote sustainable micromobility solutions. By addressing user concerns and infrastructure gaps, Lille—and similar urban areas—can improve the adoption and effectiveness of shared e-scooter systems, contributing to cleaner, more efficient urban transportation.